2022
DOI: 10.3390/molecules27196486
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Arsenic Atom of AsF3 in Five Pnicogen Bonds: Differences between X-ray Structure and Theoretical Models

Abstract: Bonding within the AsF3 crystal is analyzed via quantum chemical methods so as to identify and quantify the pnicogen bonds that are present. The structure of a finite crystal segment containing nine molecules is compared with that of a fully optimized cluster of the same size. The geometries are qualitatively different, with a much larger binding energy within the optimized nonamer. Although the total interaction energy of a central unit with the remaining peripheral molecules is comparable for the two structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…A recent study attacked this question in particular 89 taking as its base the crystal structure of AsF 3 . 90 Fig.…”
Section: Example 4types I and Ii Chalcogen Bondsmentioning
confidence: 99%
“…A recent study attacked this question in particular 89 taking as its base the crystal structure of AsF 3 . 90 Fig.…”
Section: Example 4types I and Ii Chalcogen Bondsmentioning
confidence: 99%
“…Like the other related noncovalent bonds of this type, ZBs seldom contain a first-row atom, in this case N, as the Lewis acid atom, due in large measure to its high electronegativity, which resists σ-hole formation. Although the presence of one such ZB inhibits the formation of a second such bond to the same Z atom due to negative cooperativity, the tendency toward such bonding is sufficiently compelling that two, three, and even more such bonds have been observed. …”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that such ZBs are indeed possible and are present in the crystalline forms of these molecules. Indeed, full occupation of all three σ-holes surrounding a given Z atom seems to be the norm. The large question then is whether the flattening of the C 3 -symmetric ZO 3 unit exerts any effect upon the strengths of these ZBs, and if so, to what extent. This work attempts to directly address this question by quantum chemical calculations of systems specifically chosen for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Although arsenic interactions have been studied in the context of pnicogen bonding a great deal recently, we could only identify two studies in the literature that focused on the analysis of the character and nature of arsenic interactions from a chemical bonding perspective. Politzer et al studied interactions among nitrogen, phosphorus, and arsenic-containing molecules in crystals .…”
Section: Introductionmentioning
confidence: 99%